Influence of biliary reflux on the development of GERD in children with cholelithiasis (overlap syndrome) - Pavlenko, N.; Павленко, Наталія Володимирівна; Shutova, O.; Шутова, Олена Валентинівна; Voloshin, K.; Волошин, К.В.; Solodovnichenko, I.; Солодовниченко, Ірина Григорівна; Babadzhanian, O.; Бабаджанян, Олена Миколаївна; Karpushenko, J.; Карпушенко, Ю.В. (My University, 2025)
Diseases of the upper gastrointestinal tract represent a leading problem in pediatric gastroenterology and are often associated with cholelithiasis. The present study demonstrated that biliary reflux and esophageal motor disorders play a significant role in the development and progression of gastroesophageal reflux disease (GERD) in children with cholelithiasis. Increasing severity of GERD is accompanied by enhanced biliary aggression, persistent inflammatory and erosive-ulcerative changes of the esophageal mucosa, and a higher risk of complications. The findings highlight the importance of considering the impact of biliary reflux in the diagnosis and management of combined pathology in pediatric patients.
Вплив біліарного рефлюксу на розвиток ГЕРХ у дітей хворих на жовчнокамʼяну хворобу (overlap синдром)
Співробітники кафедри педіатрії №3 та неонатології - доценти: Павленко Н. В., Шутова О. В., Солодовніченко І. Г., Бабаджанян О. М.
Keywords: children; gastroesophageal reflux disease; biliary reflux; cholelithiasis; esophageal motor disorders; 2026а/2025